Thin Film CIGS Solar Cells, Photovoltaic Modules, and the Problems of Modeling - Antonino Parisi; Luciano Curcio; Vincenzo Rocca; Salvatore Stivala; Alfonso C. Cino; Alessandro C. Busacca; Giovanni Cipriani; Diego La Cascia; Vincenzo Di Dio; Rosario Miceli; Giuseppe Ricco Galluzzo (International Journal of Photoenergy)
Starting from the results regarding a nonvacuum technique to fabricate CIGS thin films for solar cells by means of single-step electrodeposition, we focus on the methodological problems of modeling at cell structure and photovoltaic module levels. As a matter of fact, electrodeposition is known as a practical alternative to costly vacuum-based technologies for semiconductor processing in the photovoltaic device sector, but it can lead to quite different structural and electrical properties. For this reason, a greater effort is required to ensure that the perspectives of the electrical engineer and the material scientist are given an opportunity for a closer comparison and a common language. Derived parameters from ongoing experiments have been used for simulation with the different approaches, in order to develop a set of tools which can be used to put together modeling both at single cell structure and complete module levels.